2013
DOI: 10.1186/1476-4598-12-24
|View full text |Cite
|
Sign up to set email alerts
|

Short-term single treatment of chemotherapy results in the enrichment of ovarian cancer stem cell-like cells leading to an increased tumor burden

Abstract: Over 80% of women diagnosed with advanced-stage ovarian cancer die as a result of disease recurrence due to failure of chemotherapy treatment. In this study, using two distinct ovarian cancer cell lines (epithelial OVCA 433 and mesenchymal HEY) we demonstrate enrichment in a population of cells with high expression of CSC markers at the protein and mRNA levels in response to cisplatin, paclitaxel and the combination of both. We also demonstrate a significant enhancement in the sphere forming abilities of ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
191
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(214 citation statements)
references
References 52 publications
23
191
0
Order By: Relevance
“…In particular, it has been suggested that a small subpopulation of cells within tumors, called cancer stem cells (CSCs), by virtue of their relative resistance to chemotherapy may contribute to tumor recurrence (5,6). Consistent with these reports, several groups reported enrichment for CSCs when solid cancers were subjected to classical anticancer treatment (7)(8)(9)(10)(11). In accumulation, these studies suggest that significant improvement in patient outcome will require drugs that selectively target CSCs in combination with conventional chemotherapeutic regimens that target rapidly proliferating cells.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In particular, it has been suggested that a small subpopulation of cells within tumors, called cancer stem cells (CSCs), by virtue of their relative resistance to chemotherapy may contribute to tumor recurrence (5,6). Consistent with these reports, several groups reported enrichment for CSCs when solid cancers were subjected to classical anticancer treatment (7)(8)(9)(10)(11). In accumulation, these studies suggest that significant improvement in patient outcome will require drugs that selectively target CSCs in combination with conventional chemotherapeutic regimens that target rapidly proliferating cells.…”
Section: Introductionsupporting
confidence: 59%
“…An explanation for this observation is partly provided by existing reports that NACT leads to enrichment of CSCs (7)(8)(9)(10)(11)39). However, this explanation alone is not enough to reason the recurrence of tumors as the CSC subpopulation, being a part of the primary tumor itself, must get removed during surgical resection of the tumor mass.…”
Section: Discussionmentioning
confidence: 99%
“…12 Using an animal model, Abubaker et al demonstrated that short-term application of chemotherapy (cisplatin and paclitaxel) enriched the cell population with high expression of Oct-4 and CD117. 13 Similar experiments were performed by Zhou et al 14 Following the administration of cisplatin, the dormant cells of human ovarian cancer manifested an augmented expression of cells with Oct-4, nestin, CD-117, and CD44 markers, proving the resistance of this stem cell fraction to cisplatin.…”
supporting
confidence: 53%
“…7,8,13 According to Massard et al, there are 2 options for eradicating CSCs: one involves the induction of their differentiation, upon which they lose their capacity of selfreplacement (retinoic acid demonstrated such an ability); the other one involves the elimination of CSCs by targeted inhibitors of signaling pathways.…”
mentioning
confidence: 99%
“…Furthermore, ovarian CSCs may express various surface antigens, such as CD44, CD117, or CD133 (7,8,(17)(18)(19). Functionally, human ovarian CSCs apparently can form nonadherent cellular spheres, called "spheroids," which in turn are enriched for ovarian cancer cells that have high ALDH1 activity, are relatively resistant to chemotherapeutic drugs, and have enhanced potential for seeding metastatic sites or engrafting immune-deficient mice (5,17,18,(20)(21)(22).…”
mentioning
confidence: 99%